Development of Problem-Based Mathematical Learning Tools to Improve Critical Thinking Skills of Grade V Elementary School Students - Wahyu, Riska; Siswono, Tatag Yuli Eko; Sendi, Sendi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The aims of this study is to describe the feasibility of learning tools that include valid, practical, and effective, andÂ  describe the increase in students' critical thinking skills after using problem-based mathematics learning tools. This research is a development research developed with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation ). The learning tools developed in this study are the Learning Implementation Plan, teaching materials, Student Activity Sheets and evaluation. While the learning model used in this study is the Problem Based Learning (PBL) model. The results of the study show that the developed learning device is feasible, in terms of validity it meets very valid criteria with a score of 89%. The learning device developed in terms of practicality meets the very practical criteria with an average student response score of 88%. The learning tools developed in terms of effectiveness meet the criteria of being effective with an average grade completeness score of 87. Students' critical thinking skills increased after using the PBL model learning tool, indicated by a significance value of 0.000 (less than Î± = 0.05). It can be concluded that problem-based mathematics learning tools can improve the critical thinking skills of fifth grade elementary school students.